LA TRANSITION DEMOCRATIQUE MOBUTISTE FACE A L’AVENEMENT D’UNE REBELLION LIBERATRICE KABILISTE AU CONGO-ZAIRE - Tabu , Gabriel Ekili (IJRDO - Journal of Social Science and Humanities Research, 2021)
The fundamental  contradictions created by institutional  stakes  of the Mobutiste political  transition lead to the end of the latter by a rebellion carried  by ethnico-racial and the nebulous  armed  groups, for mixing  locales  unilateralized and  stranger . This illegal victorious processus of change under  Laurent-Désiré Kabila’s  leadership,drawing  lukewam  legitimacy of ideology of liberation of conglese people from  Mobutu’s  dictatorship forks dizzily towards another  kind (type) of authoritarianism  fought  paradoxically by the companions  and (sponsors) godfathers  of the « revolition ».